FGF21 Attenuates High-Fat Diet-Induced Cognitive Impairment via Metabolic Regulation and Anti-inflammation of Obese Mice - Wang, Qingzhi; Yuan, Jing; Yu, Zhanyang; Lin, Li; Jiang, Yinghua; Cao, Zeyuan; Zhuang, Pengwei; Whalen, Michael J.; Song, Bo; Wang, Xiao-Jie; Li, Xiaokun; Lo, Eng H.; et al. (Molecular neurobiology, 2018)
Accumulating studies suggest that overnutrition-associated obesity may lead to development of type 2 diabetes mellitus and metabolic syndromes (MetS). MetS and its components are important risk factors of mild cognitive impairment, age-related cognitive decline, vascular dementia, and Alzheimer’s disease. It has been recently proposed that development of a disease-course modification strategy toward early and effective risk factor management would be clinically significant in reducing the risk of metabolic disorder-initiated cognitive decline. In the present study, we propose that fibroblast growth factor 21 (FGF21) is a novel candidate for the disease-course modification approach. Using a high-fat diet (HFD) consumption-induced obese mouse model, we tested our hypothesis that recombinant human FGF21 (rFGF21) administration is effective for improving obesity-induced cognitive dysfunction and anxiety-like behavior, by its multiple metabolic modulation and anti-pro-inflammation actions. Our experimental findings support our hypothesis that rFGF21 is protective to HFD-induced cognitive impairment, at least in part by metabolic regulation in glucose tolerance impairment, insulin resistance, and hyperlipidemia; potent systemic pro-inflammation inhibition; and improvement of hippocampal dysfunction, particularly by inhibiting pro-neuroinflammation and neurogenesis deficit. This study suggests that FGF21 might be a novel molecular target of the disease-course-modifying strategy for early intervention of MstS-associated cognitive decline.